The enactment of the maternity and paternity bill 2019 of Pakistan - Sajid, Barka; Farid, Rabeya; Tabassum, Muzainah (International Journal of Scientific Reports, 2023)
“Parental leave” or “family leave” refers to a sanctioned duration off from work that is granted to both parents, irrespective of gender, to nurture a recently arrived offspring. This comprehensive terminology encompasses maternity, paternity, and adoption leave. Maternity leave is an expression of honour for the awe-inspiring physical and emotional journey experienced by mothers, simultaneously intertwining with paternity and adoption leave, which shines a spotlight on indispensable contribution of fathers. In 1919, the international labor organization (ILO) was established for the sake of providing women workers their necessary maternity leave rights. As stated in convention no. 183, maternity leave should be of at least 14 weeks or above, whereas recommendation no. 191 highlighted that leave should be of at least 18 weeks. The maternity leave can be further classified into: (a) compulsory maternity leave (CML), encompassing two weeks after birth; (b) Ordinary maternity leave (OML), spanning the initial 26 weeks of maternity leave; (c) additional maternity leave (AML) accommodating the succeeding 26 weeks of leave.